Hybrid-phase approach to achieve broadband monostatic/bistatic RCS reduction based on metasurfaces. (24th June 2020) - Wang, Chaohui; Xu, He-Xiu; Wang, Yanzhao; Zhu, Shuai; Wang, Canyu; Mao, Ruiqi
Abstract: In this paper, we propose an approach to design metasurfaces to realize superior performance for monostatic and bistatic radar cross section (RCS) reduction within a wide bandwidth. By engineering four subarrays to exhibit different hybrid focusing-linear phases within a metasurface, nearly uniform diffusive scattering can be inherently guaranteed. As an illustration, we design and fabricate a proof-of-prototype metasurface and experimentally demonstrate its wave-diffusion performances. Numerical and experimental results both show that the thin metasurface enables a monostatic/bistatic 10 dB RCS reduction over a broad bandwidth ranging from 7.2 to 17.2 GHz. In addition, more than 10 dB RCS reduction performance is preserved within a band of 7.8 ∼ 14.2 GHz even for off-normal incidence up to 60°. Our approach features broadband, polarization insensitive, wide incident angles and easy design without time-consuming optimization, promising great potentials in applications of low-scattering stealth.